2020
DOI: 10.3389/fbioe.2019.00479
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia Identification Using Multi-View Graph Measures of Functional Brain Networks

Abstract: Schizophrenia (SZ) is a functional mental disorder that seriously affects the social life of patients. Therefore, accurate diagnosis of SZ has raised extensive attention of researchers. At present, study of brain network based on resting-state functional magnetic resonance imaging (rs-fMRI) has provided promising results for SZ identification by studying functional network alteration. However, previous studies based on brain network analysis are not very effective for SZ identification. Therefore, we propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Therefore, despite the fact that in some studies the reported classification performance is relatively high [15] , [22] , in general the obtained proposed accuracy rates and suggested biomarkers are diverse [19] [21] , [23] . There are several reasons why this happens.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Therefore, despite the fact that in some studies the reported classification performance is relatively high [15] , [22] , in general the obtained proposed accuracy rates and suggested biomarkers are diverse [19] [21] , [23] . There are several reasons why this happens.…”
Section: Introductionmentioning
confidence: 78%
“…Until today, many studies have proposed several classification/diagnostic biomarkers of schizophrenia [15] [19] . A typical pipeline for the construction of FCN includes a standard preprocessing routine (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since magnetic resonance imaging (MRI) can noninvasively measure brain structural and functional changes related to brain disorder development i n v i v o , in recent years it has been widely used in the study of brain disorders [ 3 ], such as AD/MCI [ 4 , 5 ], schizophrenia [ 6 , 7 ] and autism [ 8 ]. Therefore, MRI can provide phenotypes that can be used to diagnose such disorders.…”
Section: Introductionmentioning
confidence: 99%